Online assessment: what influences students to engage with feedback?. (July 2014) - Stone, Alan
Summary Background The intention of giving written feedback is to close the gap between the standard achieved and the standard desired, but students do not always read it. Web‐based marking tools are increasingly being used in assessment practices to deliver the feedback. What motivates students to read the feedback provided, especially since the advent of these online marking tools, is poorly understood. This research looked at the factors likely to influence a medical student's engagement with written feedback delivered through an online marking tool (grademark by Turnitin). <boxed-text content-type="pullQuote" position="anchor" orientation="portrait"> What motivates students to read the feedback provided </boxed-text> <boxed-text content-type="graphic" id="tct12158-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> Methods Third‐year medical students on a UK undergraduate medical course submitted an assignment online. A questionnaire was distributed to a cohort of them following the release of their results and feedback, allowing quantitative and qualitative data collection. Software recorded whether they opened their feedback. Previous examination performance figures were also collated. Results Online feedback is accessible and acceptable to the majority of students. Personal demographics, computer literacy, previous course performance, or personal motivational drivers did not predict those who did or did not read it. Some students reported seeing little value in feedback because of their previous negative experiences. A minority found feedback hurtful, and were likely to show avoidance behaviours. Discussion: This research found that feedback provided through an online marking tool overcame many of the problems associated with handwritten feedback, but alone was not enough to ensure universal engagement. Feedback dialogues are proposed as a method to overcome negative student experiences, enhance tutor performance and encourage future student engagement.